Replacing natural aggregates with phase change material-based 3D printed aggregates in concrete for structural function and dual thermal energy storage - Gencel, Osman; Er, Yusuf; Guler, Onur; Ustaoglu, Abid; Sari, Ahmet; Subasi, Serkan; Marasli, Muhammed (Elsevier, 2026)
Extraction of natural aggregates for concrete not only depletes non-renewable resources but also causes habitat loss, groundwater disruption, and carbon emissions. At the same time, sustainable and energy-efficient construction demands materials capable of reducing operational energy. Integrating phase change materials (PCMs) into cementitious systems is promising for passive thermal regulation, yet conventional methods (microencapsulation, coatings) suffer from leakage, poor dispersion, and weak bonding. This study proposes replacing natural stone with 3D-printed smart aggregates embedding 50 wt% methyl palmitate (MP), combining structural compatibility with latent-heat storage. Concretes with natural aggregates (NA), synthetic aggregates (AA), and PCM-integrated aggregates (AAPCM) were compared in this study. At 28 days, compressive strength dropped from 92.99 MPa (NA) to 58.39 MPa (AA) and 44.34 MPa (AAPCM); ultrasonic pulse velocity decreased from 4.49 to 4.26 to 3.91 km/s. Thermal conductivity reduced by similar to 52% (1.26 -> 0.606 W/mK). DSC confirmed latent-heat storage of 224 J/g (MP) and 109 J/g (AAPCM) with >99% retention after 500 cycles. Outdoor tests showed up to 5 degrees C surface cooling and delayed heat release near 26 degrees C. Thus, PCM-integrated aggregates mitigate the environmental burden of quarrying while delivering thermally adaptive concretes, suitable for fa & ccedil;ades, pavements, and energy-resilient building envelopes.
Keywords: Phase change materials; 3D-printed aggregates; Artificial aggregate; Sustainable construction materials; Latent heat storage; Energy and energy efficiency